2015
DOI: 10.4028/www.scientific.net/msf.817.21
|View full text |Cite
|
Sign up to set email alerts
|

Hot Tearing Evaluation and Contraction Behaviors of Four AA7xxx Alloys

Abstract: The hot tearing susceptibilities (HTS) of some AA7×××alloys, AA7050, AA7055, AA7085 and AA7022 were evaluated with constrained rod casting (CRC). Thermal contraction behaviors during solidification were measured as well in a T-shaped setup. The results showed that alloys with HTS from high to low were AA7055, AA7085, AA7050 and AA7022. Zn content in 7××× aluminum alloys seemed to play a major role with respect to the HTS index. Remarkable differences could be seen on thermal contraction behaviors within solidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The rating of the amount of linear contraction for the four alloys is given as AA7022 < AA7050 < AA7085 < AA7055. [10] Here, this linear contraction is compared with the hot tearing predictions below. Compared with other alloys, AA7022 has the lowest Cu content and the highest Mg content, and its Zn content is closer to 4 to 6 wt pct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rating of the amount of linear contraction for the four alloys is given as AA7022 < AA7050 < AA7085 < AA7055. [10] Here, this linear contraction is compared with the hot tearing predictions below. Compared with other alloys, AA7022 has the lowest Cu content and the highest Mg content, and its Zn content is closer to 4 to 6 wt pct.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Besides these factors, alloy composition is another crucial point to affect the hot tearing susceptibility. Bai et al [10,11] investigated the hot tearing and thermal contraction behavior of several commercial 7xxx alloys. It was found that different alloys exhibited different hot tearing resistance.…”
Section: Introductionmentioning
confidence: 99%